2007
DOI: 10.1152/ajplung.00240.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and lung inflammatory effects induced by systemically administered diesel exhaust particles in rats

Abstract: Pollution by particulates has consistently been associated with increased cardiorespiratory morbidity and mortality. It has been suggested that ultrafine particles, of which diesel exhaust particles (DEP) are significant contributors, are able to translocate from the airways into the bloodstream in vivo. In the present study, we assessed the effect of systemic administration of DEP on cardiovascular and respiratory parameters. DEP were administered into the tail vein of rats, and heart rate, blood pressure, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 51 publications
3
70
1
9
Order By: Relevance
“…Reductions in pulmonary function have also been reported following occupational exposures in chronic studies (Rudell et al, 1996). In addition, diesel PM has been associated with changes in heart rate, increased incidence of arrhythmias, impairment of vasodilation, increase in blood pressure, and systemic inflammation (Hazari et al, 2011;Peretz et al, 2008;Tornqvist et al, 2007;Nemmar et al, 2007;Carll et al, 2013;Harkema et al, 2009;Knuckles et al, 2011). Human studies by Mills et al (2005Mills et al ( , 2007aMills et al ( , 2007b) demonstrated a dose-dependent increase in prothrombotic effects and acute myocardial ischemia upon exposure to diesel exhaust.…”
Section: Bd Ce Further Studies Are Required To Understand What Combumentioning
confidence: 98%
“…Reductions in pulmonary function have also been reported following occupational exposures in chronic studies (Rudell et al, 1996). In addition, diesel PM has been associated with changes in heart rate, increased incidence of arrhythmias, impairment of vasodilation, increase in blood pressure, and systemic inflammation (Hazari et al, 2011;Peretz et al, 2008;Tornqvist et al, 2007;Nemmar et al, 2007;Carll et al, 2013;Harkema et al, 2009;Knuckles et al, 2011). Human studies by Mills et al (2005Mills et al ( , 2007aMills et al ( , 2007b) demonstrated a dose-dependent increase in prothrombotic effects and acute myocardial ischemia upon exposure to diesel exhaust.…”
Section: Bd Ce Further Studies Are Required To Understand What Combumentioning
confidence: 98%
“…These techniques can be considered as semi‐quantitative space‐resolved imaging methods. TEM visualizes the intracellular localization of NMs in ultra‐thin (50–100 nm) sections of tissue or cultured cells 29, 30. Chemical identification of NMs can be done by X‐ray energy‐dispersive spectrometry (EDS) and electron energy‐loss spectrometry (EELS) in TEM.…”
Section: Label‐free Dosimetry and Imaging Techniques—toward High Thromentioning
confidence: 99%
“…Ultra-fine particles are more likely to enter circulation and are associated with the major oxidative and pro-inflammatory effects of PM [1]. Particles of nano-sized dimension, as small aggregates of carbonaceous particles less than 100 nm, constitute the most part of DEP [2] and represent the greatest concern to human health because they remain in the atmosphere for long periods, invade the indoor air environment, and can be breathed most deeply into the lungs where they are likely to be more toxic than coarse particles [3]. The exposure of animal and human subjects to DEP for experimental purposes has clearly shown the oxidant and pro-inflammatory nature of DEP [4] as a direct consequence of their ability to induce reactive oxygen species (ROS) and oxidative stress [5].…”
Section: Introductionmentioning
confidence: 99%